Immunopathological characteristics of patients with bullous pemphigoid and neurological disease. (26th March 2013) - Taghipour, K.; Chi, C.‐C.; Bhogal, B.; Groves, R.W.; Venning, V.; Wojnarowska, F.
Abstract Background The relationship between bullous pemphigoid (BP) and neurological disease has been the subject of numerous recent studies and BP antigens and their isoforms have been identified in the central nervous system (CNS). Whilst epidemiological data support this association, little is known about the pathomechanism behind this link and the immunological characteristics of patients with BP and neurological disease, other than multiple sclerosis (MS), has not been studied. Objective We aimed to compare the cutaneous immune response in BP patients with and without neurological disease, to investigate whether or not there is a distinctive immunopathological profile in patients with concomitant BP and neurological disease. Methods Seventy‐two patients with BP were included and divided into two groups; those with neurological disease (BP+N, n = 43) and those without (BP−N, n = 29). Patients in BP+N group had a confirmed neurological disease by a hospital physician, neurologist or psychiatrist with positive neurological imaging where appropriate, or a Karnofsky score of 50 or less due to mental impairment. All sera were analysed with indirect immunofluorescence (IIF) using serial dilutions up to 1:120000, immunoblotting (IB) and Enzyme‐linked immunosorbent assay (ELISA) for BP180 and BP230. Results Median antibody titres by IIF were 1:1600 vs. 1:800 for BP−N and BP+N, respectively, although the difference did not reach statistic significance (P = 0.93, Mann–Whitney U‐test). ELISA values for both BP180 and BP230 did not differ significantly between the two groups. Similarly, autoantibodies to specific antigens as identified by ELISA and IB were not related to the presence of neurological disease. Conclusion The results of this study indicate that patients with BP and neurological disease exhibit an immune response to both BP180 and BP230, thus the link between the CNS and the skin is not dependent on a specific antigen, but possibly both antigens or their isoforms may be exposed following a neurological insult, and play a role in generation of an immune response.